2008
DOI: 10.1097/mnm.0b013e3282f30598
|View full text |Cite
|
Sign up to set email alerts
|

The role of bone scintigraphy in treatment planning, and predicting pain relief after kyphoplasty

Abstract: Bone scanning is an excellent predictor of response to kyphoplasty and decreases the number of vertebrae to be treated as suggested by X-ray. Preoperative bone scanning is recommended to avoid incorrect selection of treatment level. Even when the appropriate level has been selected an incomplete response can be expected if additional chronic fracture is seen on bone scanning. In the event of unexpected incomplete response, re-evaluation with bone scanning may demonstrate new disease amenable to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The literature about outcome predictors for BKP is scarce and rather focuses on preoperative diagnostics and patient selection in a sense that cases with a bone edema detectable on MRI or scintigraphy were experiencing very good pain relief [15,16]. Investigations for VP are more numerous.…”
Section: Discussionmentioning
confidence: 99%
“…The literature about outcome predictors for BKP is scarce and rather focuses on preoperative diagnostics and patient selection in a sense that cases with a bone edema detectable on MRI or scintigraphy were experiencing very good pain relief [15,16]. Investigations for VP are more numerous.…”
Section: Discussionmentioning
confidence: 99%
“…48 Kyphoplasty is most successful at restoring the height of the fractured vertebral body if it is performed within 3 months of the occurence of fracture or onset of pain. 22,23,43,49,50 Short-term results show that 85% to 100% of patients have good to moderate pain relief. 26, 48 Wardlaw et al found that kyphoplasty had improved functional recovery compared with nonsurgical treatment.…”
Section: Operative Managementmentioning
confidence: 99%
“…Bone scans may not become positive at the fracture site until about 10 days after the initial injury, and if the bone scan is obtained too early in the process, a falsenegative result may occur. 303 …”
Section: Radiographic Evaluationmentioning
confidence: 99%